Hellboy in Hell. [Volume 2], Death card - Mignola, Mike (Dark Horse Books, 2016)
"After facing off for a second time against the Vampire of Prague, Hellboy seeks the help of an incompetent team of doctors. As he explores, Hellboy gets a glimpse of the new World Tree that he helped to create, stands accused of murder by his own sister and, in a way, brings about the destruction of Pandemonium itself"--Provided by publisher.